P252 Accurate measurement of lung function in the workplace and potential effects of underestimation. (15th November 2016) - Sumner, JE; Robinson, E; Codling, A; Lewis, L; Wiggans, RE; Bradshaw, LM; Barber, CM; Warren, N; Forman, S; Fishwick, D
Abstract : Introduction: Accurate workplace spirometry measurement is key to giving workers the best clinical assessment of their respiratory health. We were interested in the underestimation of spirometry that occurs if best practice is not adhered to and the significance of this on assessment of health at work. Methods: 667 stone, brick and foundry workers (with varying spirometry experience), carried out lung function testing as part of a larger cross sectional workplace study. Each performed a minimum of 3 forced expirations. Testing continued until each worker had met the ATS/ERS guidance. The final FEV1 and FVC recorded was the maximum value attained from 3 technically acceptable blows, and that the two highest FEV1 and FVC values were within 150 mls. Using the final FEV1 and FVC for each worker, it was then possible to calculate the underestimate of both measures, had only the first blow, or the maximum of the first two blows, been used for interpretation. Results: 613 of the 669 (91.6%) attained the ATS/ERS criteria based on FEV1 . Analysis of the first actual blow, regardless of technical quality, showed an FEV1 mean underestimate of 250 mls (median = 80 mls, IQR = 210 mls). If only the first technically acceptable blow had been carried out, the FEV1 would have been underestimated by a mean of 114 mls (60 mls, 150 mls). If only two technically acceptable blows had been carried out, and the maximum of these used, the FEV1 would have been underestimated by a mean of 36 mls (0 mls, 50 mls). Similarly, the FVC would have been underestimated by a mean of 131 mls (75 mls, 180 mls) if only the first technically acceptable blow had been used for interpretation. If only two technically acceptable blows were carried out, the FVC would have been underestimated by a mean of 43 mls (0 mls, 50 mls). Conclusion: Non adherence to ATS/ERS lung function testing guidance at work can cause the FEV1 and FVC to be underestimated by clinically significant amounts.